ROLE OF RECIPROCAL FILIAL PIETY IN THE RELATIONSHIP BETWEEN PARENTAL INVOLVEMENT AND FILIAL BEHAVIOR AMONG MALAYSIAN ADOLESCENTS - Nainee, Sarvarubini; Soon Aun, Tan; Chee Seng, Tan (Journal of Techno-Social, 2016)
Filial piety is a central quality of cultural practices in a family which includes obedience and honoring of one’s parents and it is considered as the fundamental element to practice in the Malaysian family system. Of late, the young generation perceives caring for the elderly as a burdensome task, which can be observed by the rising number of old folks centers. Parenting styles strongly predict the obligation of filial piety among young adolescents. Generally, adolescents who are more filial may be more attached to their parents. Filial piety formed among this group of people can be traced to how they were brought up in their family which affects the individual’s self-obligation towards their parents. Recognizing the influence of parenting on the filial behavior of adolescents, the present study addressed the importance of parents’ involvement in influencing filial behavior among Malaysian adolescents. This study involved a total of 405 school students aged between 14 to 17 years old, selected from two urbanized and metropolitan cities of Peninsular Malaysia using a cluster sampling method. A self-administrated questionnaire was used to collect the data of the study. The findings of the study indicate that parental involvement (father and mother) significantly correlates with reciprocal filial piety and filial behavior. Moreover, reciprocal filial piety correlated significantly with filial behavior. The present study denotes that reciprocal filial piety plays a mediating role in the relationship between parents’ involvement (father and mother) and filial behavior. Therefore, parental warmth and support are important to promote and enhance filial practices at home among adolescents.